Strategy Creative MSMEs of Ropih Art House in supporting the Creative Economy in the Creative Economy in the Braga, Bandung City - Indri Ferdiani Suarna; Muhammad Caesar Fadhillah; Lia Nuraeni (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the business model of creative MSMEs in the field of painting, focusing on the experience and strategies implemented by Mr. Dede, a painting entrepreneur who has been running this business since 1992. The method used in this study is an in-depth interview with the informant to gain an understDedeng of the initial process, challenges, marketing strategies, and expansion plans faced in running a painting business. The results of the study show that although the painting business relies on creativity and uniqueness of the product, external factors such as technological developments, market competition, and marketing through social networks play an important role in the sustainability and growth of the business. In addition, market expansion and adaptation to market changes through the use of online platforms are crucial factors in expDedeng reach and increasing revenue. In conclusion, success in the painting business is highly dependent on the ability to innovate, build long-term relationships with customers, and adapt to market and technological developments.